Successful treatment of anastomotic leakage with an intestinal obstruction catheter and stent by colonoscopy: a case report and brief literature review - Huang, Wang; Tan, Zhenzong; Sun, Hao (Frontiers in Oncology, 2024)
BackgroundAnastomotic leakage (AL) is one of the most common, severe, and difficult-to-treat complications after colorectal cancer surgery. However, to date, the best treatment options for AL remain elusive.Case descriptionHere, we report the case of a 70-year-old man who had previously undergone Hartmann’s surgery and developed a large AL after a colostomy reversal surgery in an external hospital. The condition mainly manifested as passage of the fecal material through the abdominal drainage tube accompanied by fever after intestinal surgery. We used a new method involving a transanal obstruction catheter combined with an anastomotic stent, along with fasting, administration of parenteral nutrition, and anti-infection treatment. By following this approach, AL was successfully cured without any complications.ConclusionTo the best of our knowledge, this is the first case of the use of a transanal intestinal obstruction catheter combined with an anastomotic stent for treating colorectal AL; the findings may guide clinicians to better treat and manage AL.